Hierarchical Structures and Dynamic Incentives - Dongsoo Shin; Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
We study the optimal hierarchical structure of an organization under limited commitment. The organization cannot make a long term commitment to wages and output levels, while it can commit to its hierarchical structure. We show that the optimal hierarchical structure is horizontal when it is highly likely that the employees are efficient or inefficient. By contrast, when such likelihood is intermediate or output does not expand very fast over time, the optimal hierarchical structure is vertical - with a vertical hierarchy, the organization can mitigate dynamic incentive problems linked to limited commitment.
urn:nbn:de:bvb:19-epub-13236-0
Keywords: D82; D86; 330; Dynamic Incentives; Organization Design; Organisationsstruktur; Arbeitsorganisation; Ökonomischer Anreiz; Leistungsanreiz; Motivation; Theorie